2013
DOI: 10.4238/2013.november.18.13
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of the zona pellucida 3 (ZP3) gene during ovarian development and the location of ZP3 protein in oocytes in a natural, wild triploid crucian carp mutant, Carassius auratus var. Pingxiangnensis

Abstract: ABSTRACT. Carassius auratus var. Pingxiangnensis (designated CaP), distributed in the Pingxiang region of Jiangxi Province, China, is a natural, wild triploid crucian carp mutant that has two reproductive development modes: gynogenesis and bisexual reproduction. Little information is available about the expression pattern of the zona pellucida 3 (ZP3) gene during ovarian development and the location of the ZP3 protein in oocytes of this fish. In this study, we obtained the full-length cDNA of ZP3 (CaP_ ZP3). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Pcc-zp2 was highly significant in brain, hepatopancreas, kidney, ovary, and spleen tissues, and these results were the same as those reported in the rare minnow. Ovarian-specific zp2 was found in zebrafish, crucian carp, and goldfish (Mold et al, 2001;Shi et al, 2013), and zp was found in both the hepatopancreas and ovary tissues of medaka and pufferfish (Kanamori et al, 2003). The results of the present study suggested that Pcc-zp2 is associated with the ovarian/hepatic-shared expression pattern.…”
Section: Tissue-specific Distribution Of the Target Genessupporting
confidence: 53%
See 1 more Smart Citation
“…Pcc-zp2 was highly significant in brain, hepatopancreas, kidney, ovary, and spleen tissues, and these results were the same as those reported in the rare minnow. Ovarian-specific zp2 was found in zebrafish, crucian carp, and goldfish (Mold et al, 2001;Shi et al, 2013), and zp was found in both the hepatopancreas and ovary tissues of medaka and pufferfish (Kanamori et al, 2003). The results of the present study suggested that Pcc-zp2 is associated with the ovarian/hepatic-shared expression pattern.…”
Section: Tissue-specific Distribution Of the Target Genessupporting
confidence: 53%
“…Gene expression profiles in different genders (Hale et al, 2011), tissues, and developmental stages (Ijiri et al, 2008;Shi et al, 2013) may have dual functions in sex determination and differentiation. The present study detected all four gene catalogues associated with tissue-specific and temporal distributions in Pcc.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of this expression to the female red junglefowl demonstrates the relevance of this expression to female reproduction. In other oviparous vertebrates, these proteins are found in the liver either in addition or instead of the ovary [ 37 , 38 ]. In birds, extra gonadal expression of ZP1 was reported in the liver of quail [ 31 ], where it was also shown that intravenously injected ZP1 incorporates into the perivitelline membrane [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA was treated with RNase-free DNase I (Promega, USA) to eliminate genomic DNA contamination. 23,24) cDNA was synthesized using the Transcriptor First Strand cDNA Synthesis Kit (Promega, USA). RTqPCR was performed using a real-time PCR SYBR Green detection system (Eppendorf).…”
Section: Rt-qpcrmentioning
confidence: 99%